THE SHADOW ECONOMY AND ITS IMPACT ON A COUNTRY’S FINANCIAL POTENTIAL - Nadiia Davydenko; Ivan Olifer; Natalia Wasilewska; Mirosław Wasilewski (Polityki Europejskie, Finanse i Marketing)
The aim of the article is to reveal the essence of the shadow economy and its impact on the financial potential of a country. We have discovered that the shadow economy is an objective phenomenon which is inherent in the economic systems of all countries, and that its level is determined by the level of development of the economic system, the difficulty of identifying all possible variants of the shading processes, and the moral and cultural characteristics of the country. It has been established that the shadow economy plays a major role in developing countries and that the level of the shadow economy in advanced economies is significantly lower. Thus, due to the results of the correlation-regression analysis, an inverse relationship between the level of GDP and the shadow economy was established. A system of measures aimed at preventing and combating corruption is proposed.